A Discussion about the Need for New Regulations in Tourism - Cybula, Piotr; Zawistowska, Hanna (Studia Oeconomica Posnaniensia, 2017)
In the article with the example of the act on tourist services and the EU Directive 2015/2302 was used to focus on the problems of the needs and possibilities of the introduction of new regulations in tourism. The authors drew attention to the essential impact EU law has on the shape and scope of national legislation. The existence of EU legislation, which is the result of the division of legislative powers between the EU and the member countries, entails a significant limitation of the freedom of regulation at national level. This causes the necessity to determine, prior to legislative action, whether, and if so to what extent, a given issue is regulated by EU law. The problem of the limitation of the freedom of legal regulation on the domestic level was illustrated with the example of the EU Directive 2015/2302 and the act on tourism services. The problem of the limitation the freedom of legal regulation on the domestic level was illustrated with the example of the EU Directive 2015/2302 and Polish act on tourism services.